Techniques and Instruments for Psychomotor Domain Assessment - M. Ferry Irawan; Mamkua Amirullah (Mentari : Journal of Islamic Primary School, 2025)
This article is based on the importance of assessment in the domain of skills. In evaluating psychomotor learning outcomes, assessments can be conducted through performance tests that measure the skills mastered by students. Performance assessment is carried out by observing students' activities as they perform certain tasks. This type of assessment is suitable for measuring the achievement of competencies that require students to perform specific tasks such as prayer practice, sports practice, or role-playing. The techniques and instruments used in evaluating psychomotor learning outcomes include rating scales, checklists, and anecdotal records. The analysis of psychomotor learning evaluation instruments can be conducted both theoretically (qualitative analysis) and empirically (quantitative analysis).